Effects of punching force on cutting tool in forming process using FEA approach - Ahmad Khairul Hafizi, Wahab (2009)
This thesis deals with sheet metal forming process. There are two main objectives of this research, firstly, to analysis the cutting tool wear in different force of punching and clearance and the second objective is to predict the critical part or part that will wear first on the cutting tool. In sheet metal forming process, quality of product and minimize the production cost is very important. The tool wear will affect the quality of product and increase the production cost of manufacturing. In the ALGOR simulation, the tool wear will determined by analyse stress on cutting tool. In addition, the wear tool would be high as stress at the cutting edge was extremely high. This project will considered punch force and clearance between punch and die to analysis the tool wear. The punching force used for this project are 100kN, 140kN and 180kN. The range of percentage used for clearance between punch and die used in this project are between 1.70% to 3.3%. These two parameters which are the punch force and clearance is very important for tool life and the final product.